2017
DOI: 10.1111/apha.12973
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐214‐3p: A link between autophagy and endothelial cell dysfunction in atherosclerosis

Abstract: miR-214-3p regulates ox-LDL-initiated autophagy in HUVECs by directly targeting the 3'UTR of ATG5 and may have a suitable role in the pathogenesis of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 33 publications
1
50
1
Order By: Relevance
“…miR‐126 alleviates ox‐LDL‐induced HUVECs injury through restoring autophagy flux via repressing PI3K/Akt/mTOR pathway and further implicates the potential therapeutic targets to reverse AS . miR‐214‐3p regulates ox‐LDL‐initiated autophagy in HUVECs by directly targeting the 3′‐UTR of ATG5 and may have a suitable role in the pathogenesis of AS . The development and function of macrophages are shaped by micro‐environmental signals, which drive macrophage differentiation, with the M1 (promote inflammation) and M2 (inhibit inflammation) populations being the two extreme phenotypes of the macrophage polarization spectrum.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…miR‐126 alleviates ox‐LDL‐induced HUVECs injury through restoring autophagy flux via repressing PI3K/Akt/mTOR pathway and further implicates the potential therapeutic targets to reverse AS . miR‐214‐3p regulates ox‐LDL‐initiated autophagy in HUVECs by directly targeting the 3′‐UTR of ATG5 and may have a suitable role in the pathogenesis of AS . The development and function of macrophages are shaped by micro‐environmental signals, which drive macrophage differentiation, with the M1 (promote inflammation) and M2 (inhibit inflammation) populations being the two extreme phenotypes of the macrophage polarization spectrum.…”
Section: Introductionmentioning
confidence: 93%
“…111 miR-214-3p regulates ox-LDL-initiated autophagy in HUVECs by directly targeting the 3 0 -UTR of ATG5 and may have a suitable role in the pathogenesis of AS. 112 The development and function of macrophages are shaped by micro-environmental signals, which drive macrophage differentiation, with the M1 (promote inflammation) and M2 (inhibit inflammation) populations being the two extreme phenotypes of the macrophage polarization spectrum. Threose nucleic acid (TNA) is refractory to nuclease digestion and capable of undergoing Darwinian evolution to produce aptamers with affinity to specific targets.…”
Section: Mirs Regulate Autophagy In Atherosclerosismentioning
confidence: 99%
“…7 On the other hand, the present manuscript by Wang et al shows that miR-214-3p overexpression repressed autophagy in the endothelial cells from mouse aorta. 1 The underlying molecular mechanisms linking decreased autophagy to endothelial dysfunction in atherosclerosis were investigated by Wang and et al 1 These results seem to be contradictory to those described above, but an explanation may be that in generally miRNAs have many targets and their functions can be different depending on the state of target cells or their co-factors including other miRNAs and proteins in extracellular vesicles. Thus, it has been demonstrated that endothelial cells secrete miR-214-enriched exosomes, which suppress senescence and stimulate endothelial cell migration and angiogenesis in vitro and in vivo.…”
mentioning
confidence: 94%
“…The authors showed in their experimental study three very important aspects: (i) in atherosclerotic mouse model, they identified an inverse correlation between miR-214-3p and ATG5 and ATG12; (ii) in young HUVEC, they found ox-LDL-induced autophagy as evidenced by the increases in ATG5, ATG12 and microtubule-associated protein 1 light chain 3 (LC3B) protein levels with a simultaneously decreased SQSTM1/p62 protein level, and miR-214-3p overexpression reduced autophagy; (iii) in old HUVECs, inhibition of the miR-214-3p increased their protective autophagy response to the ox-LDL stimulus, as evaluated by autophagic protein analysis, LC3B immunofluorescence assay and transmission electron microscopy (TEM). 1 The microRNAs (miRNAs), small non-coding RNA molecules, are posttranscriptional regulators of gene expression by their action on target mRNAs controlling their translation and degradation, modulating in this way various cellular and developmental processes. 2 They have a substantial contribution to cardiovascular physiology and pathology, and their abnormal expression has been associated with atherosclerosis and cardiovascular diseases, they being involved in the putative mechanisms that lead to endothelial dysfunction and vascular damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation